PERILAKU KEPUTUSAN PEMBELIAN KONSUMEN BERDASARKAN KUALITAS PRODUK DAN PERSEPSI HARGA - Vanessa, Angelica; Tjiptodjojo, Kartika Imasari (FEB Universitas Sam Ratulangi Manado, 2024)
People living in tropical climates require extra skin care through the use of sunscreen that is applied regularly, especially on the face. The use of sunscreen can prevent direct sun exposure that can damage the facial skin layer. Many sunscreen products are on the market so consumers are faced with various choices of quality and price offered. This study aims to analyze the product quality and price perceptions of Azarine sunscreen products that influence the purchasing decision process. This research was conducted with non-probability sampling with a research sample of people in Bandung who have bought and used Azarine sunscreen, totaling 120 respondents. This study found that product quality and price perceptions influence purchasing decisions.